Estudo da viabilidade do reaproveitamento da areia de caldeira na produção de argamassas - Pedron, Vitor Felipe Pavin [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Sand is a finite material and widely used in construction, so one day there may be a shortage, and this work studies the possibility of partially or totally replacing the use of natural sand, which would be favorable to prevent the extraction of sand from natural environments and would also give a suitable destination to the boiler sand that often ends up being discarded. This report presents the results of experiments carried out with the intention of analyzing the viability of such substitution within the mortar, the boiler sand was obtained in a partnership with the company Fibria, and the analysis of the boiler sand was made through the tests of granulometry, specific mass, compression resistance and flow table. The boiler sand presented gains in compressive strength at all ages of rupture, presented a consistency index similar to natural sand, specific mass slightly lower than natural sand, and granulometry less well distributed than natural sand. Therefore, the results obtained were favorable to the replacement of natural sand by boiler sand, not showing any significant negative factor for the replacement of natural sand.

A areia é um material finito e amplamente usado em construções, portanto um dia poderá haver escassez, e este trabalho estuda a possibilidade de substituir parcialmente ou totalmente o uso da areia natural, o que seria favorável no sentido de prevenir a extração da areia de ambientes naturais e daria um destino adequado à areia de caldeira que muitas vezes acaba sendo descartada. Esse trabalho apresenta o resultado de experimentos realizados com intenção de analisar a viabilidade de tal substituição dentro da argamassa, a areia de caldeira foi obtida em uma parceria com a empresa Fibria e a análise da areia de caldeira foi feita através dos ensaios de granulometria, massa específica, resistência à compressão e índice de consistência. A areia de caldeira apresentou ganhos nas resistências à compressão em todas as idades de ruptura, apresentou um índice de consistência similar à areia natural, massa específica ligeiramente inferior à areia natural, e granulometria menos bem distribuída que a areia natural. Portanto, os resultados obtidos foram favoráveis à substituição da areia natural pela areia de caldeira, não apresentando nenhum fator expressivamente negativo para a substituição da areia natural.
Viability study of the reuse of boiler sand in the production of mortars
Keywords: Boiler sand; Residual sand; Pulp Industry; Sand replacement; Areia de caldeira; Areia residual; Indústria celulose; Substituição areia